The 2nd International Electronic Conference on Biomedicines 2023
DOI: 10.3390/ecb2023-14290
|View full text |Cite
|
Sign up to set email alerts
|

Review of Research in Developing Hydrogels with Insulin to Promote Wound Healing

Aneta Ostróżka-Cieślik,
Marcin Przybyła,
Weronika Wójcik
et al.

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…At the beginning of the 20th century, there was a growing interest in insulin as a potential active substance to accelerate the regeneration of damaged skin. In our previous article, we reviewed studies published between 2000 and 2022 on the therapeutic efficacy of a hydrogel form of insulin for skin application [1]. The analysis confirms the efficacy of this hormone in the treatment of hard-to-heal wounds without causing side effects such as hypoglycemia.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…At the beginning of the 20th century, there was a growing interest in insulin as a potential active substance to accelerate the regeneration of damaged skin. In our previous article, we reviewed studies published between 2000 and 2022 on the therapeutic efficacy of a hydrogel form of insulin for skin application [1]. The analysis confirms the efficacy of this hormone in the treatment of hard-to-heal wounds without causing side effects such as hypoglycemia.…”
Section: Introductionmentioning
confidence: 86%
“…The topical application of insulin can reverse the impairment of diabetic wound regeneration processes and promote wound healing. The therapeutic effect of insulin after topical administration is mainly due to its role in regulating oxidative stress and inflammatory responses [1][2][3][4]. Chen et al [5] found that insulin is involved in the early recruitment of neutrophils, increase in F2 macrophages and IL-10 levels [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, this hormone has also been known for its skin regenerative properties. In addition to its great wound-healing effects, insulin is one of the cheapest growth factors to obtain biotechnologically, which is of significant value when it comes to producing dressings with this hormone on a large scale [1,2]. It has been confirmed that topical administration of insulin stimulates keratinocyte proliferation and migration in the wound tissue, depending on the dose and exposure time of the peptide.…”
Section: Introductionmentioning
confidence: 99%